2015
DOI: 10.1002/prot.24949
|View full text |Cite
|
Sign up to set email alerts
|

Archeal lectins: An identification through a genomic search

Abstract: Forty-six lectin domains which have homologues among well established eukaryotic and bacterial lectins of known three-dimensional structure, have been identified through a search of 165 archeal genomes using a multipronged approach involving domain recognition, sequence search and analysis of binding sites. Twenty-one of them have the 7-bladed β-propeller lectin fold while 16 have the β-trefoil fold and 7 the legume lectin fold. The remainder assumes the C-type lectin, the β-prism I and the tachylectin folds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Lectins in which one, two or all three of the Greek keys in the fold carry a binding site are known (Sharma et al, 2007;Chandran et al, 2013). From careful sequence comparisons, it was suggested that Mevo lectin has only one binding site (Abhinav et al, 2016) situated on the Greek key comprising the N-and C-terminal stretches of the polypeptide chain (Table 1). Repeated attempts to solve the structure by molecular replacement using various -prism I lectin subunits and their oligomers as search models did not succeed, presumably on account of poor homology or inadequate structural similarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectins in which one, two or all three of the Greek keys in the fold carry a binding site are known (Sharma et al, 2007;Chandran et al, 2013). From careful sequence comparisons, it was suggested that Mevo lectin has only one binding site (Abhinav et al, 2016) situated on the Greek key comprising the N-and C-terminal stretches of the polypeptide chain (Table 1). Repeated attempts to solve the structure by molecular replacement using various -prism I lectin subunits and their oligomers as search models did not succeed, presumably on account of poor homology or inadequate structural similarity.…”
Section: Resultsmentioning
confidence: 99%
“…One domain of life, namely the archaea, had remained a virgin area in terms of lectin research. Recently, we identified 46 putative lectin/lectin-like domains through a bioinformatics search of 165 archaeal genomes (Abhinav et al, 2016). Criteria based on sequence and structure indicate that they are distributed among six structural families involving sevenbladed -propeller, -trefoil, legume lectin, C-type lectin, -prism I and tachylectin folds.…”
Section: Introductionmentioning
confidence: 99%
“…Archea run counter to bacteria in their genetic and biochemical constitution and was recognized as a province of life distinctly different from two other domains bacteria and eukaryotes (plants, animals, fungi and protists). Lectins from Archea were first reported by Vijayan (Abhinav and Vijayan 2016). They screened 165 archeal genomes of 78 different species.…”
Section: Archeal Lectinsmentioning
confidence: 99%
“…Given the variation of glycans and their potential as unique identifiers it is no wonder that early immune signaling employed carbohydratebinding lectins to decipher microbially complex environments. Lectins have been identified in the genomes of almost every organism, functioning in numerous biological pathways (Abhinav et al, 2016, Xia et al, 2017, Breitenbach et al, 2018. The evolutionary ramification of lectins has resulted in over 20 different families that have been classified based on their saccharide binding specificity and structure of the carbohydrate recognition domains, many of which are present in D. discoideum (Eichinger et al, 2005).…”
Section: Microbiome Control By Lectinsmentioning
confidence: 99%